Pre-Treatments Effect on Pepper Drying Time and Microstructure - Ana Sakura, Zainal Abidin; Melissa Michelle, Rolland; Sinin, Hamdan; Rasli, Muslimen; Shirley, Jonathan Tanjong; Raudhah, Ahmadi; Shahrol, Mohamaddan; Annisa, Jamali (AIP Publishing, 2023)
. The traditional pepper drying process takes 4 to 5 days, although it can take longer on wet day. This paper presented a study on the effects of two pre-treatment methods to the improvement of drying rate of black pepper production. Boiling and chilling were used to pre-treat two samples of pepper berries respectively. To avoid microbial infections, the samples must be dried quickly after pre-treatment. Each sample was then spun in a rotary drum drier at a predetermined temperature to achieve this. The weight of the sample was recorded at regular interval until it reached moisture content of 12%. The physical and chemical characteristics of each sample were also checked using Fourier Transform Near Infrared (FT-NIR). The surface morphology of the skin and core of the samples were observed using Scanning Electron Microscopy (SEM). When compared to untreated samples, pre-treated samples took less time to dry. The dried core of the pre-treated samples revealed less damaged than the untreated sample when microstructural alterations were seen using SEM. This study found that pre-treating pepper berries before drying reduced drying time from 8 hours to 2½ hours (based on untreated sample). The moisture percentage of dried pre-treated samples was similarly within the acceptable range. Thus, the application of rotary drum dryer to dry the pre-treated pepper is the novelty to this research.